Content analysis of “Financial accounting knowledge” articles from the beginning until now - Haji Molla Hosseini, Hamzeh; Borhani, Seyyed Abbas (International Journal of Business Management and Entrepreneurship, 2023)
Purpose: The purpose of this study is to know the content characteristics of the articles in issues 1 to 41 of "Financial Accounting Knowledge" magazine. Method: The current research is a qualitative and descriptive research and content analysis technique was used to analyze the data. Results: The findings of the research indicate that 78% of the authors were male and 22% were female. 28% of the authors of assistant professor articles and the rest of the academic levels have obtained a lower position. Al-Zahra and Tehran universities have been the most active universities in creating works. In terms of subject matter, 49% of the articles were in the field of financial accounting and the rest were in other fields. Conclusion: Examining the gender distribution of the authors of the articles indicates that the role of men is more than 4 times greater than that of women in the production of articles in this magazine. The organizational affiliation of the producers of the printed articles shows that the majority of the authors of the articles of this publication are affiliated with the prestigious scientific centers of the country. The thematic analysis of the articles published in the journal indicates the commitment of the journal to its defined specialized areas. Examining the frequency distribution of the scientific rank of the authors of the articles shows that the assistant professors are in the first position of producing articles, which is probably due to the issues related to the promotion of the professors. Contribution: After about 12 years of this publication, it is necessary to evaluate its activities. The analysis of the content of this publication can provide an objective picture of its existing conditions, and it also shows thematic trends and possible shortcomings in the articles of this publication.